Penerapan Metode K-Nearest Neighbor Untuk Pemilihan Rekomendasi Game FPS Pada Aplikasi Google Play Store - Puji Pangestu; Resad Setyadi (Journal of Information System Research (JOSH), 2023)
Game or game is a recreational activity with the aim of having fun, hobbies and free time. Games or games are usually done alone or together. Electronic games or better known as virtual games are games that use electronic media, which is entertainment in the form of multimedia that is made as attractive as possible so that players can get something so that there is inner satisfaction. Many game lovers are enthusiastic about the development of the game industry, including FPS games. FPS stands for "First Person Shooter" which means Indonesian, namely "Frames Per Second" which means it is a game that displays an Image/Frame within 1 second, usually FPS is more widely used in filmmaking, animation, CGI (Computer Generated Imagery). ) and games. However, many problems in installing games do not pay attention to hardware specifications, especially storage (memory) and RAM, this is very influential for game quality, therefore a decision support system is made using the K-Nearest Neighbor (KNN) method. The purpose of this study is to produce a recommendation for selecting FPS games using the K-Nearest Neighbor method according to the specifications according to the wishes of the players.